Effectiveness of Cold Compress on Pain Management in Patients with Superficial Burn Injury: A Systematic Review - Dwi Puji Lestari; Lisa Isdaryanti; Luh Gede Wirani Riskayanti Darmawan; I Made Dwi Budhiasa Ari Serengga; Kiki Fajar Nurhidayah; Herdina Mariyanti (Indonesian Journal of Global Health Research, 2025)
Superficial burns often cause acute pain that interferes with patient comfort. One of the non-pharmacological methods used to reduce pain is cold compresses, but scientific evidence regarding their effectiveness is still mixed. To evaluate the effectiveness of cold compresses in reducing pain in patients with superficial burns. This systematic review was conducted by searching articles from the Scopus, PubMed, and ScienceDirect databases using the keywords: "cold compress", "burn injury", "pain management", "superficial burns", "RCT". The inclusion criteria were RCT articles published between 2015–2024, in English, and discussing the effects of cold compresses on pain in superficial burns. Selection was carried out through the PRISMA process. Of the 1,025 articles found, 14 articles met the inclusion criteria. Each article underwent title and abstract screening, followed by full-text assessment for eligibility. Methodological quality was then appraised using the JBI Critical Appraisal Tool, and only studies with moderate to high quality were included in the synthesis to ensure robust and reliable findings. The majority of studies showed that cold compresses significantly reduced the intensity of acute pain in the early phase of superficial burns (p < 0.05). This effect was reported to be effective especially in the first 24 hours after injury, with minimal side effects. Cold compress is an effective, safe, and easy-to-do nonpharmacological intervention to reduce pain in superficial burn patients. This intervention deserves to be part of standard care in emergency departments and primary health care.